2013
DOI: 10.1073/pnas.1300117110
|View full text |Cite
|
Sign up to set email alerts
|

A unified selection signal for attention and reward in primary visual cortex

Abstract: Stimuli associated with high rewards evoke stronger neuronal activity than stimuli associated with lower rewards in many brain regions. It is not well understood how these reward effects influence activity in sensory cortices that represent low-level stimulus features. Here, we investigated the effects of reward information in the primary visual cortex (area V1) of monkeys. We found that the reward value of a stimulus relative to the value of other stimuli is a good predictor of V1 activity. Relative value bia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

20
164
3

Year Published

2014
2014
2018
2018

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 154 publications
(196 citation statements)
references
References 51 publications
(85 reference statements)
20
164
3
Order By: Relevance
“…Indeed, our data demonstrate that punishment can induce sensitivity for low-level stimulus features in early sensory cortex, as previously shown for high rewards (Stanisor et al, 2013) in a way that new stimuli that share those features will also benefit from enhanced sensory processing in V1. However, Our data do not allow to specify the exact stimulus feature(s) for which this plasticity occurred.…”
Section: Role Of Stimulus Familiarity (See Figure 4 Panels B and C)supporting
confidence: 82%
See 1 more Smart Citation
“…Indeed, our data demonstrate that punishment can induce sensitivity for low-level stimulus features in early sensory cortex, as previously shown for high rewards (Stanisor et al, 2013) in a way that new stimuli that share those features will also benefit from enhanced sensory processing in V1. However, Our data do not allow to specify the exact stimulus feature(s) for which this plasticity occurred.…”
Section: Role Of Stimulus Familiarity (See Figure 4 Panels B and C)supporting
confidence: 82%
“…First, the task parameters could account for this unexpected finding, which might be partly due to the presentation of stimuli in isolation (i.e., neutral and rewarded stimuli are not presented simultaneously), while most effects of reward on sensory processing have been observed in competitive contexts (e.g., Serences, 2008), where prioritization effects are obviously maximized. Furthermore, given that the recognition task heavily depended on feature-based attention, the influence of reward might have been overshadowed by the effects of voluntary feature-based attention allocation on early visual processing (Lee and Shomstein, 2013;Stanisor et al, 2013), that was presumably set to perform the task. Second, it is also possible that the use of monetary reinforcers might have played a role in the divergence between learning speed and neural changes in early visual cortex.…”
Section: Role Of Stimulus Familiarity (See Figure 4 Panels B and C)mentioning
confidence: 99%
“…Amygdala neurons initially detect a visual stimulus and may code its identity and then transition within 60 -300 ms to differential reward value coding (9,422,428). V1 and inferotemporal cortex responses show initial visual stimulus selectivity and only 50 -90 ms later distinguish reward values (371,557). Thus there is a sequence in the processing of external events that advances from initial detection via identification to valuation.…”
Section: Dopamine Event Detection Responsementioning
confidence: 99%
“…One study in monkeys found that V1 neurons with a strong value effect also exhibited a strong attention effect, suggesting overlap between relative value and top-down attention (Stanisor et al, 2013). Interestingly, Baruni and collaborators (2015) conducted a study in monkeys in order to differentiate reward expectation from attentional source of modulation in visual area V4.…”
Section: Value-based Modulation In Visual Cortex Of Human and Nonhumamentioning
confidence: 99%